2021
DOI: 10.3390/s21020407
|View full text |Cite
|
Sign up to set email alerts
|

A Prosthetic Socket with Active Volume Compensation for Amputated Lower Limb

Abstract: Typically, the actual volume of the residual limb changes over time. This causes the prosthesis to not fit, and then pain and skin disease. In this study, a prosthetic socket was developed to compensate for the volume change of the residual limb. Using an inflatable air bladder, the proposed socket monitors the pressure in the socket and keeps the pressure distribution uniform and constant while walking. The socket has three air bladders on anterior and posterior tibia areas, a latching type 3-way pneumatic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Unfortunately, rehabilitation is especially difficult for transfemoral amputees, and research indicates that a high amputation level is associated with both prosthetic non-use and a decreased probability of remaining ambulatory [ 2 , 3 ]. Socket fit has been cited as one of the main factors affecting gait re-education, rehabilitation, and quality of life for amputees from the viewpoint of both amputees and clinicians [ 4 , 5 , 6 , 7 , 8 , 9 ]. Poor socket fit is the cause of at least one gait deviation, in people with lower limb amputation, which could be linked to premature long-term musculoskeletal degenerations [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, rehabilitation is especially difficult for transfemoral amputees, and research indicates that a high amputation level is associated with both prosthetic non-use and a decreased probability of remaining ambulatory [ 2 , 3 ]. Socket fit has been cited as one of the main factors affecting gait re-education, rehabilitation, and quality of life for amputees from the viewpoint of both amputees and clinicians [ 4 , 5 , 6 , 7 , 8 , 9 ]. Poor socket fit is the cause of at least one gait deviation, in people with lower limb amputation, which could be linked to premature long-term musculoskeletal degenerations [ 6 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We expect that the use of distance sensing and the practice of not placing the sensing elements on the actuators are two key reasons the auto-adjusting socket in this study performed better than other systems described in the literature. [4][5][6][7][8][9][10][11][12][13] Distance sensing may be more effective than pressure sensing because the measurement is very sensitive to small changes in socket fit, and presence of the sensors does not disrupt the regular limb-socket interface. 18 We did not consider placing the sensing elements on the actuators an appropriate strategy.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several research groups extended from this work to pursue electronic automatic size-adjusting sockets that used a powered actuator to change socket size and a pressure sensor for feedback control. [4][5][6][7][8][9][10][11][12][13][14] A handful achieved a closed-loop control system, [5][6][7]10,13 but only Pirouzi et al 5 tested a system on people with lower limb amputation. Pirouzi et al 5 demonstrated that vertical limb displacement at the posterior brimline of the socket varied linearly with actuator pressure during standing with cyclic weight bearing, suggesting that actuator pressure could be used to control vertical limb displacement.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that air bladders may have the potential of providing comfort and less load on the medial crest bone and end of tibia bone with superior fitting and low contact pressure. 23,24 Although there is no other study in the literature that assessed pressure reductions across different subregions of the residual limb, previous studies have illustrated that volumetric changes in the socket through manual tightening or releasing of a dial button, clamp, or lacing system 6,25 have the potential to reduce excessive pressure concentrations of the residual limb. Nonetheless, these previous approaches were limited because of the fact that they require the control of the user and assistance from the prosthetists (no automation), which may cause patients to excessively tighten their socket owing to the desire of maximizing the fit and stability of the prosthesis.…”
Section: Discussionmentioning
confidence: 99%